전자스패클패턴 간섭시스템을 이용한 피로하중을 받는 균열선단에서 탄소성 영역 측정에 관한 연구 - 김경수(KYUNG-SU KIM); 심천식(CHUN-SIK SHIM) (Han-guk haeyang gonghak hoeji (Online), 2002)
The magnitude of the plastic zone around the crack tip of DENT(Double Edge Notched Tension) specimen and the crack growth length under cyclic loading were measured by ESPI(Electronic Speckle Pattern Interferometry) system. The measured magnitude of plastic zone was compared with the equations proposed by Irwin and calculated by a nonlinear static method of MSC/NASTRAN. The measured crack growth length by ESPI system was also compared with the obtained data by the image analysis system. From the study, it is confirmed that the plastic zone and crack growth length can be measured accurately with the high-tech equipment.